Food waste anaerobic biogas slurry as fertilizer: Potential salinization on different soil layer and effect on rhizobacteria community. (1st May 2022) - Meng, Xingyao; Zeng, Bei; Wang, Pan; Li, Jinglin; Cui, Ruoqi; Ren, Lianhai
Highlights: Biogas slurry reframing the salinity distribution in topsoil for 90 days application. Cl - is the key potential environmental risk indicator in food waste BS. Cl - 、Ca 2+ and Mg 2+ were potential enriched in 1 ∼ 4 cm topsoil. Salinity from biogas slurry damage the balance of rhizobacteria. Abstract: Biogas slurry(BS) from food waste anaerobic fermentation coexisted a lot of salinity that could damage soil and crops health. So, this study was to explore the effect of the application of biogas slurry on soil salinization in 1 ∼ 4 cm, 4–6 cm and 6 ∼ 8 cm soil layers every 10 days, Chinese cabbage growth and rhizobacteria. The results indicated that ≤ 10% concentration of biogas slurry was uninjurious for soil and plant, the dry weight growth rate was 73.7% compared with CK, long term application should be further evaluated the potential risk of salinity on underground water and human health. As for high concentration of biogas slurry ≥ 10% concentration of biogas slurry could inhibit the seed germination and root elongation, and the germination percentage was declined from 87.6% to 2.4%, but 50% and 100% concentration of biogas slurry showed a promotion of crop growth because of sufficient nutrition. However, the potential accumulation of salinity could be seen in high concentration of biogas slurry for long term application especially in top1-4 cm soil. Correlation analysis showed that Cl - was the main factor resulting high EC in all soil layers. 16S rRNA sequencing showed that UCG-004, Ketobacter, Sphingopyxis and RB41 could be regard as the indicators for determining the potential jeopardize on soil environmental by high salinity from biogas slurry.